Efikasi Diri Berhubungan dengan Kepatuhan Manajemen Diri pada Pasien Diabetes Melitus di Wilayah Kerja Puskesmas Buleleng III - Ni Komang Desi Tri Handayani; Putu Wira Kusuma Putra; Ida Ayu Agung Laksmi (Jurnal Ilmu dan Teknologi Kesehatan, 2019)
Diabetes mellitus is a group of metabolic diseases with characteristics of hyperglycemia that occur due to abnormal insulin secretion and insulin performance. Prevention of the occurrence of DM complications can be done by obediently doing good self-management behavior. Self-management compliance of good diabetes mellitus can achieve success if individuals have the knowledge, skill, and self-efficacy to manage diabetes mellitus. Self-efficacy determines how a person feels, thinks, motivates himself, and behaves from time to time. This study aimed to determine the correlation between self-efficacy and self-management compliance of diabetes mellitus patients. This study used the Cross-Sectional approach with a number of samples was 139 respondents. The sample selection used nonprobability sampling, especially purposive sampling. Data collection tools used questionnaires. Self-efficacy could be measured using the general self-efficacy questionnaire (GSE) and self-management compliance could be measured using the DSMQ (Diabetes Self-Management Questionnaire). Data analysis used Spearman Rank correlation analysis. The results obtained that p-value 0,0001 (p <0,05), therefore it could be concluded that there was a correlation between self-efficacy and self-management compliance of diabetes mellitus patients. Researchers suggest that health care workers can help patients with diabetes mellitus in improving their self-efficacy by providing motivation and IEC regarding patients’ self-management with diabetes mellitus.